A Flow of Reversal Study in Opposing Free and Forced Convective Flow in a Vertical Tube - Tsang, Brian K. (My University, 1975)
Flov reversal conditions in the turbulent opposing convection regime were investigated in the cooling of upflow water and the data correlated by the equation: Gr/(Re^2.58)=0.053/Pr for 6 ≤ (L/d) ≤ 18. The Metais-Eckert plot, which depicts the region of natural/forced convection interaction effects on the heat transfer coefficient, was found to be unsuitable for correlating the conditions for which flow reversal occurs because of the improper inclusion. of the parameter (d/L).
Title: A Flow of Reversal Study in Opposing Free and Forced Convective Flow in a Vertical Tube, Author: Brian K. Tsang, Location: Thode